IMPLEMENTASI PENYELESAIAN PERKARA BERBASIS E-COURT DAN E-LITIGASI MENURUT PERMA NOMOR 1 TAHUN 2019 (STUDI KASUS DI PENGADILAN AGAMA MALANG) - Mar’atus Sholikah; Khoirul Asfiyak; Faridatus Sa’adah (Jurnal Hikmatina, 2022)
E-court is a court instrument as a form of service to the community in terms of online case settlement. The Malang Religious Court is a court that has implemented e-court since November 28, 2018 which initially referred to RERMA number 3 of 2018 and changed to PERMA Number 1 of 2019, but the Malang Religious Court has not yet received an e-court award certificate, thus raising the purpose of research to to describe the implementation of e-court and e-litigation, and to describe the application of e-court in realizing case administration services effectively and efficiently. This study uses a qualitative approach and the type of case study research, data collection techniques used are non-participant observation, semi-structured interviews and documentation. The results of the study show that the process of implementing e-Court and e-litigation is already running according to where the account creation process for Other Users is carried out in court and for Registered Users it is carried out independently via the web, case registration is online, down-payment of fees that have been detailed automatically in e-court, summoning the parties for a trial, and conducting the trial until the decision. And the application of e-court in realizing case administration services effectively and efficiently, namely: realizing the simple principle, the fast principle, the low cost principle in litigation.